Structural transformation of LDCs: Past performance and future challenges - United Nations Economic; Social Commission for Asia; the Pacific (Asia-Pacific Sustainable Development Journal, 2024)
The objective of this paper is to provide an analysis on how structural transformation of the economies of least developed countries (LDCs) since the establishment of the category in 1971 has been contributing to their development. To do this, changes in the sectoral composition of their output, employment and exports, and developments in labour productivity are analysed. LDCs have become increasingly differentiated, between regional groups and within themselves, and major factors underpinning this divergence are examined. The results indicate the challenges these countries face in sustaining and accelerating their development and the policy priorities required to reach this goal.